At Home With Spelling 2 - Coates, Deirdre; Illustrated by Ray and Burrows, Corrine (New York Oxford University Press, 1997)
Provides the Spelling workbooks for KS1 of "New Oxford Workbooks". This book introduces and practises all the necessary spelling rules, in systematic sequence, for children to work through individually at home. The author of this book teaches dyslexic children in London.
Include Illustrations
Keywords: English language -- English language--Orthography and spelling--Study and teaching (Elementary) -- Early childhood education